The Role of the Nunatsiavut Heritage Forum in the Development of Community Archaeology - Rankin, Lisa; Brake, Jamie; Onalik, Lena; Andersen, Joan; Flowers, Marjorie; Flowers, Nicholas; Igloliorte, David; Shiwak, Inez; Shiwak, Anthony (Études Inuit Studies, 2022)
The Nunatsiavut Heritage Forum, held annually since 2010 and overseen by the Nunatsiavut Government Archaeology Office, brings together people involved in heritage work from all five constituent Inuit Communities as well as interested public to discuss issues of concern and set goals to address them. It has rapidly become the primary venue for public engagement on heritage matters as well as the planning and practice of archaeology in the territory. The forum is held in a different community each year, providing an opportunity to celebrate the unique history of each hamlet and prioritize their specific needs. Archaeology, the request for specific local projects, and how they are undertaken, have been discussed at each forum to date. In 2015, a SSHRC-supported partnership grant between the Nunatsiavut Government and Memorial University called Tradition and Transition Among the Labrador Inuit was created to address community heritage concerns and interests raised through the forum by partnering archaeologists and other heritage specialists with communities to help Nunatsiavut meet these goals. Today, as the partnership draws to a close, we reflect back on what has been accomplished, what has been learned, and how we might move forward together.